Cohort Study of the Success of Controlled Weight Loss Programs for Obese Dogs. (1st October 2015) - German, A.J.; Titcomb, J.M.; Holden, S.L.; Queau, Y.; Morris, P.J.; Biourge, V.
Abstract : Background: Most weight loss studies in obese dogs assess rate and percentage of weight loss in the first 2–3 months, rather than the likelihood of successfully reaching target weight. Objective: To determine outcome of controlled weight loss programs for obese dogs, and to determine the factors associated with successful completion. Animals: 143 obese dogs undergoing a controlled weight loss program. Methods: This was a cohort study of obese dogs attending a referral weight management clinic. Dogs were studied during their period of weight loss, and cases classified according to outcome as "completed" (reached target weight), "euthanized" (was euthanized before reaching target weight), or "stopped prematurely" (program stopped early for other reasons). Factors associated with successful completion were assessed using simple and multiple logistic regression. Results: 87/143 dogs (61%) completed their weight loss program, 11 [8%] died or were euthanized, and the remaining 45 [32%] stopped prematurely. Reasons for dogs stopping prematurely included inability to contact owner, refusal to comply with weight management advice, or development of another illness. Successful weight loss was positively associated with a faster rate ( P < .001), a longer duration ( P < .001), and feeding a dried weight management diet ( P = .010), but negatively associated with starting body fat ( P < .001), and use of dirlotapide ( P = .0046). Conclusions and Clinical Relevance: Just over half of all obese dogs on a controlled weight loss program reach their target weight. Future studies should better clarify reasons for success in individual cases, and also the role of factors such as activity and behavioral modification.